Hydrology : advances in theory and practice - Quinn, N. W. (Nevil Wyndham) (In focus, 2020)
Hydrology: Advances in Theory and Practice, brings together contributions to both the theory and practice of hydrology, including chapters on (amongst other topics) flood estimation methods and hydrological modelling. The book also looks forward with a global hydrology research agenda fit for the 2030s, and explores how to make advances in hydrological modelling - based on almost 50 years of modelling experience. In Focus - a book series that showcases the latest accomplishments in water research. Each book focuses on a specialist area with papers from top experts in the field. It aims to be a vehicle for in-depth understanding and inspire further conversations in the sector.